RECOLONIZING FORMAL RESTORATIVE JUSTICE: A SOCIO-LEGAL CRITIQUE OF INDONESIA’S SHIFT FROM CUSTOMARY JUSTICE TO STATE LAW - Ardian Kurniawan; Hendri K.; Syamsu Hadi; Anggi Purnama Harahap; Burhanuddin Burhanuddin (Diponegoro Law Review, 2025)
This study critically examines the legal dynamics of restorative justice (RJ) implementation in Indonesia, focusing on the marginalization of customary legal systems as a result of state-driven formalization. While RJ is normatively intended to promote reconciliation and community-based dispute resolution, its centralization particularly through prosecutor-led Restorative Justice Houses has led to the symbolic domestication of indigenous justice practices. The central legal issue addressed in this study is the recolonization of customary law within the framework of state-administered RJ, which systematically weakens the roles of traditional mediators such as hakam and ninik mamak. Employing an empirical juridical method and a socio-legal approach, this research draws on field data from Jambi Province and offers comparative insights from RJ practices in New Zealand, Canada, and Rwanda to uncover the tension between formal legal norms and living customary law. The findings suggest that Indonesia’s RJ model reflects a form of legal recolonization rather than genuine legal pluralism. This article proposes a hybrid legal model that substantively empowers indigenous justice mechanisms within a plural legal framework. The main contribution of this research lies in its decolonial critique of state dominance in RJ practices and its proposal for a multilevel reconstruction strategy local, national, and international, that institutionalizes customary-based justice. The study is limited by its geographical scope and the absence of quantitative evaluation. Future research is encouraged to broaden regional coverage and empirically assess the effectiveness of hybrid legal models in balancing state authority with community autonomy.